Closing of the Krishna Basin: irrigation, streamflow depletion and macroscale hydrology - Biggs, Trent W.; Gaur, Anju; Scott, C.; Thenkabail, Prasad S.; Gangadhara Rao, Parthasaradhi; Gumma, Murali K.; Acharya, Sreedhar; Turral, Hugh (International Water Management Institute, 2007)
Discharge from the Krishna River into the ocean decreased by 75 percent from 1960-2005, and was zero during a recent multi-year drought. This paper describes the physical geography and hydrology of the Krishna Basin, including runoff production and a basic water account based on hydronomic zones. More than 50 percent of the basin's irrigated area is groundwater irrigation, which is not currently included in inter-state allocation rules. Future water allocation will require inclusion of the interactions among all irrigated areas, including those irrigated by groundwater and surface water.